Development of Students Learning Module for Disaster and Environmental Knowledge Subject for Undergraduate Students of Universitas Syiah Kuala - RM Teguh Prawira Atmaja*; Sulastri Sulastri; Nazli Nazli (Universitas Syiah Kuala, 2021)
Disaster education is an essential part of disaster mitigation steps in shaping character and building a culture of disaster preparedness. Knowledge on Disaster and Environmental (PKL) is a general course taught at the Undergraduate level at Syiah Kuala University. This research and development aim to produce valid, effective, and practical modules for PKL. The research and development model used in this study is an adaptation of the research and development steps proposed by Borg Gall, and the learning design model used in the initial product planning stage adapting the model proposed by Dick Carey. Expert validation and student readability test were followed to confirm the quality of the module. Three expert validators were involved, and 24 students were enrolled in several questionnaire-based approach of their perspective to the pre-and post-revision product module. The results of this study created a PKL learning module that has valid value (score 4.01-4.33), and the average results on the student readability test were in the good category (score 4.13-4.56). The final product that has been revised according to input and suggestions from the validator has the quality for exemplary utilization.